Microleakage of Bulk-Fill Composites at Two Different Time Points - Kianvash Rad, Niloofar; Javid, Bahar; Panahandeh, Narges; Ghasemi, Amir; Kamali, Ali; Mohammadi, Gholamhasan (Journal of Dental School, 2019)
Objectives: Microleakage is the main concern in composite restorations. This study aimed to compare the microleakage of two bulk-fill and one conventional composite at two different time points. Methods: Class II cavities were prepared in 60 premolar teeth and divided into six groups of 20. Groups 1 and 4 were incrementally filled with Grandio composite. Groups 2 and 5 were filled with X-tra fil bulk-fill composite. Groups 3 and 6 were filled with Tetric-N-Ceram bulk-fill composite in one layer. The samples were thermocycled for 5000 cycles between 25-55°C. In groups 1-3, the samples were incubated for 24 hours and then immersed in 1% methylene blue dye. Groups 4-6 were incubated for three months and then immersed in dye. All samples were mesiodistally sectioned and degree of microleakage was scored under a light microscope. The data were analyzed using Mann Whitney and Kruskal-Wallis tests. Results: The results showed no significant difference among groups 1-5 and 6 in terms of microleakage (P>0.05) but a significant difference was noted between groups 1 and 4 in this regard (P=0.01). The microleakage in groups 4-6 was higher than that in groups 1-3 (P=0.02). Also, microleakage in gingival margins was greater than that in occlusal margins (P=0.02). Conclusion: The microleakage of bulk-fill composites is comparable to that of conventional composites both at 24 hours and three months after restoration.